The influence of warehouse management system on product quality in Pantai Timor Hypermarket, Kelantan - Winnie Wong Zing Zing; Siti Nur Nadiah M.Suhaimi; Lin Kar Fai (2023)
Over the last few decades, the global business environment has changed rapidly and profoundly. The market has become increasingly complex, requiring companies to become increasingly competitive. Now that the new market trends are changing rapidly, it increased the market competitiveness which it leads the company to a permanent decrease in the ability to respond efficiently and quickly (Luo et al, 2022). Companies are being inundated with complex data, and those who can turn it into useful information will have a competitive advantage (Luo et al, 2022). The overall supply chain process and its improvement are directly influenced by the warehouse's role, the performance of which is determined by its management and the strategy with which the warehouse is managed in terms of capacity, organisation, and the process procedures followed by warehouse operators. A warehouse's primary goal is to manage the movement and storage of goods in the most efficient way possible while also providing flexibility in resource management. According to Vatumalae et al., the primary structure of the warehouse will be the freightage section for distribution and receiving, while the excess or remaining product will be stored in the warehouse for a limited time (2020). Warehouse Management monitors the movement of products through the warehouse. The effectiveness of warehouse management will put the retail chain distribution company ahead of their competitors and set a high standard to compete.